A Case of Type 2 Hypersensitivity to Rasburicase Diagnosed with a Natural Killer Cell Activation Assay - Viel, Sébastien; Pescarmona, Rémi; Belot, Alexandre; Nosbaum, Audrey; Lombard, Christine; Walzer, Thierry; Bérard, Frédéric (Frontiers in Immunology, 2018)
Drug hypersensitivity reactions can lead to different clinical pictures depending on the underlying immunological mechanism. Diagnosis tests are already available to assess the most frequent drugs hypersensitivity reactions, which are mediated by specific IgE or T cells. However, it remains challenging to diagnose type 2 hypersensitivity reactions (T2HR), which can lead to severe cytopenia and liver failure. Here, we describe a case of T2HR to rasburicase, an uricolytic agent used to prevent tumor lysis syndrome. In this patient, sensitization was associated with the production of specific IgG able to bind to leukocytes. We found that patient NK cells were specifically activated in the presence of rasburicase and autologous serum, which led to exocytosis of lytic granules. This antibody-dependent cell cytotoxicity mechanism may lead to cytopenia observed in the patient. Moreover, this NK cell activation assay could be used to improve the diagnosis of a T2HR to rasburicase and, by extent, to other drugs. These data also suggest that NK cells could play an important role in the pathophysiological mechanism of T2HR.